Investigating the Trend of the Great Slaty Woodpecker (Mulleripicus pulverulentus) Population Status in Western Nepal - Deelip Chand Thakuri; Hari Basnet; Laxman Prasad Poudyal; Prakash Chandra Aryal (Ecology and Evolution)
ABSTRACT The Great Slaty Woodpecker (Mulleripicus pulverulentus) has experienced a rapid population decline due to the loss of primary forest habitats across its range. Despite being classified as globally Vulnerable, detailed information regarding its status and distribution is largely insufficient and outdated. To address this, we conducted surveys from 2019 to 2021 in the western Terai Arc Landscape of Nepal, covering 29 transects, each 5 km long, to estimate the present population status, tree size of cavity trees, and overall distribution of the species in Nepal. We measured the diameter at breast height (DBH) within meter circular plots of 15 m radius at each woodpecker sighting location to explore the relationship between tree diameter and woodpecker presence. Additionally, we modelled the potential distribution of the habitat of Great Slaty Woodpecker across Nepal using available occurrence points. A total of 81 individuals were recorded across 14 transects, with 66 individuals within protected areas and 15 outside. Our findings demonstrated a direct correlation between tree DBH and woodpecker presence, indicating that large trees are critical for the species, with an average DBH of 61.26 cm for cavity trees where woodpeckers excavated cavities. Furthermore, we found that the total suitable habitat for the species in Nepal is approximately 6738 km2, with a significant portion located outside protected areas. The habitat in community forests and outside protected areas is particularly vulnerable to selective logging, posing a threat to the species. Therefore, further studies on the impact of logging on the Great Slaty Woodpecker are essential for effective conservation strategies.